Evaluation the Effect of Amine Type on the Non-isothermally Derived Activation Energy for the Interaction of 3 Antidepressant Drugs with Lactose - Faranak Ghaderi; Mahboob Nemati; Mohammad Reza siahi-shadbad; Hadi valizadeh; Farnaz Monajjemzadeh (Tabriz University of Medical Sciences, 2019)
Purpose: Evaluation of drug-excipients compatibility is an important stage during preformulation studies. In the present research, differential scanning calorimetry (DSC) at different heating rates (2.5, 10, 15°C/min) was applied for the kinetic evaluation of fluvoxamine (FLM), sertraline (SER) and doxepin (DOX) binary mixtures with lactose. Methods: Solid state kinetic parameters of the mixtures were calculated using two different thermal methods including ASTM E698 and Starink and the effect of amine type (pKa value) was investigated based on the calculated activation energies. Results: Based on obtained results mean activation energy calculated for FLM, SER and DOX with lactose using ASTM E698 and Starink methods are equal to 335.23, 132.02 and 270.99 kJ/ mol respectively. Conclusion: Results showed that the probability of drug-lactose interaction is higher in the SERlactose mixture in comparison with other two antidepressant drugs which is consistent with their pKa values.